The Journey to a Wider Understanding of Ways of Knowing: Knowledge Translation and the Arts (LEARNing Landscapes, 2019)
In this commentary, educator and author Katherine Boydell reflects on her journey to incorporate art genres in the research process as a knowledge translation strategy for producing and disseminating research-informed knowledge. She highlights the need to move beyond descriptions of form and content to grapple with the unique methodological, theoretical, and ethical challenges of working with research participants, artists, and audience members engaging in this work. She describes some of her current arts-based research and identifies the current pressures to conform to expectations regarding “what counts” in academia and concludes with future suggestions to advance arts-based knowledge translation.
Keywords: arts-based research; experiential research; embodiment; arts-based knowledge translation